The Effect of Differences Feeding Time of Natural Food Artemia sp. and Water Flea on the Growth and Survival of Giant Gouramy Larvae (Osphronemus gouramy, Lac) - Haerizul Fahrullah; Netti Aryani; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in May to June 2016 in the Laboratory of Fish Hatchery and Breeding Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this research was to know The Effect of Differences feeding time of Natural Feed Artemia sp. and Water Flea on the Growth and Survival of Giant Gouramy Larvae (Osphronemus gouramy, Lac). This research used the experimental method, while the experimental design that was used completely randomized design (CRD) with five treatments and three replication. The treatments in this research ware P1 (giving Artemia sp. for 10 days and 30 days for Water Flea), P2 (giving Artemia sp. for 20 days and 20 days for Water Flea), P3 (giving Artemia sp. for 30 days and 10 days for Water Flea), P4 (giving Artemia sp. for 40 days), P5 (giving Water Flea for 40 days).The result showed the best treatment was feeding with P5 (Giving Water Flea for 40 days) the growth of absolute weigh that produces 0,086 grams, the growth of absolute length is 0,831 cm, the daily growth rate of 4,332 %. The water quality parameters during research were temperature 26,4-27,8 ºC, pH 6,5-7,3 and dissolved oxygen 4,0-6,0 ppm.Key words: Natural food, Osphronemus gouramy, growth, and survival